The Triple Whammy: Gendered Careers of Geographically Marginalised Academic STEM Women (International Journal of Gender, Science and Technology, 2018)
In this paper we explore how gender, non-standard job roles as well as location create a triple whammy affecting the visibility and therefore the career paths of women STEM academics. Drawing on data from interviews and surveys at a distributed university with locations across the UK, we examine the experiences of a group of ‘Regional Academics’ who are located at a distance from the main university campus, either in regional centres or as homeworkers, and show how gender intersects with distance and status to exacerbate inequalities. In their narrative accounts, they describe themselves as the ‘glue that hold the bits of the university together’, mediating between part-time tutors, students and other academics and researchers. We explore how career progression has been limited for these liminal academics, but how small steps to increase visibility and provide recognition for achievement can result in strategies that overcome these inherent obstacles.